PENINGKATAN KETERAMPILAN BERPIKIR KRITIS SISWA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING KELAS X DPIB 1 DI SMK NEGERI 2 MEDAN - Ardiani, Ricka; Nirmawan, Nirmawan (Universitas Islam Sumatera Utara, 2023)
This research discusses the improvement of critical thinking skills in the activity of analyzing linguistic rules in biographical texts using the problem based learning model. The problem based learning learning model is a learning model that puts forward problems to be solved with high thinking skills. The purpose of this assessment is to find out the effectiveness of applying the problem-based learning model in improving thinking skills in analyzing linguistic rules in biographical texts in class X DPIB 1 SMK Negeri 2 Medan. In this classroom action research it was carried out through cyclical stages. The results of obtaining scores in the pre-action stage with the achievement of an average score of 50.90. Achievement of the average value in the first cycle with an achievement value of 72.30. Achievement of the average value of the second cycle with a value of 85.48. The implementation of improving students' thinking skills in analyzing linguistic rules in biographical texts is very appropriate by using the problem-based learning model and experiencing a very significant increase in each cycle. This research discusses the improvement of critical thinking skills in the activity of analyzing linguistic rules in biographical texts using the problem based learning model. The problem based learning learning model is a learning model that puts forward problems to be solved with high thinking skills. The purpose of this assessment is to find out the effectiveness of applying the problem-based learning model in improving thinking skills in analyzing linguistic rules in biographical texts in class X DPIB 1 SMK Negeri 2 Medan. In this classroom action research it was carried out through cyclical stages. The results of obtaining scores in the pre-action stage with the achievement of an average score of 50.90. Achievement of the average value in the first cycle with an achievement value of 72.30. Achievement of the average value of the second cycle with a value of 85.48. The implementation of improving students' thinking skills in analyzing linguistic rules in biographical texts is very appropriate by using the problem-based learning model and experiencing a very significant increase in each cycle.